Genomic analysis and lysogenic conversion of novel RAP44-like phages in Riemerella anatipestifer - Junxuan Zhang; Xiaolu He; Jinzhen Hao; Yefan Wang; Jinyang Su; Xiaoxin Chen; Liying Deng; Yizhang Zheng; Zixing Guo; Mianzhi Wang; Yongxue Sun (Poultry Science)
Riemerella anatipestifer, an important waterfowl pathogen, causes severe economic losses because of limited prevention and control methods. We aimed to characterize the prophages of R. anatipestifer and explore their role in lysogenic conversion and fitness cost to host bacteria based on the interactive infection of 110 wild-type strains and ATCC 11845. The temperate phages PJA1, PJO17, PJR4, PJL1, and PJX6 were isolated from clinical strains and showed various lytic abilities, high similarity between different Riemerella phages, and stable properties in transmission electron microscopy, temperature sensitivity, and one-step growth curve detection. To study the effects of lysogeny, we developed five lysogenic strains by integrating phages into the genome of JW1, a wild-type and prophage-absent strain of R. anatipestifer that is particularly susceptible to phage infection. The spontaneous induction frequency of the lysogen strains reached approximately 4-log, showing resistance to each other. Genomic analysis revealed high similarity to the first characterized Riemerella phage, RAP44, particularly in structural gene modules. Lysogens exhibited resistance to superinfection by prophages, similar to the reference strain ATCC 11845. Compared to JW1, lysogens showed consistent growth curves and colony morphology but were significantly thicker and shorter in scanning electron microscopy images. The lysogenic conversion process reduced the minimum inhibitory concentration of rifampin for lysogen JW1_PJA1 and JW1_PJO17 to 1/4 and 1/8 of that observed in the strain JW1, respectively, and decreased the MIC of florfenicol for lysogen JW1_PJR4 to half of the original value. Genomic comparisons revealed prophage integration and sequence rearrangement in lysogen genomes under the action of integrase. Co-culture experiments demonstrated that sensitive JW1 could be lysogenized by phages that were spontaneously induced from lysogens. Given the high prevalence of prophages in R. anatipestifer and no significant growth defect under laboratory conditions, lysogenic conversion appears to be a natural adaptation of this pathogen. By elucidating how prophages affect R. anatipestifer resistance and fitness, our findings provide a foundation for harnessing these interactions to design effective phage-based control strategies.